Avaliação de vacinas contra Mycoplasma hyopneumoniae em suínos e camundongos - Marchioro, Silvana Beutinger (2013)
Mycoplasma hyopneumoniae (M. hyopneumoniae) is the causative agent of enzootic pneumonia (EP) in pigs, a chronic respiratory disease characterized by low mortality and high morbidity, responsible by significant economic losses in the pig industry worldwide. M. hyopneumoniae infection can be controlled by optimizing management practices and housing conditions, as well as with the use of antibiotics and vaccination. Commercial vaccines consist of adjuvanted inactivated whole cell preparations, and are frequently used worldwide in countries with an intensive pig production. The currently available vaccines are beneficial from an economic point of view, but they do not provide a sustainable control of the disease. They cannot prevent colonization of M. hyopneumoniae in the respiratory tract, and do not significantly reduce the transmission of the pathogen. Also, little is known about the exact mechanisms of the partial protection they induce. In this context, the general aims of this thesis were to assess the mode of the action of an existing commercial vaccine on the one hand and to develop and evaluate a new recombinant vaccine against M. hyopneumoniae on the other hand, looking for more effective strategies for disease control. For development of the recombinant vaccine a chimeric protein was developed and evaluated. This protein was based on proteins known to play a role in the adhesion and that were able to induce an immune response and a partial protection against M. hyopneumoniae infection when evaluated individually. From the studies described in this thesis, it can be concluded that intramuscular vaccination with an adjuvanted bacterin is able to stimulate both systemic and local immune responses, and that the new recombinant vaccine developed against EP might be promises strategies to control the disease.